UBE2C Overexpression Aggravates Patient Outcome by Promoting Estrogen-Dependent/Independent Cell Proliferation in Early Hormone Receptor-Positive and HER2-Negative Breast Cancer - Kim, Yu-Jin; Lee, Gyunghwa; Han, Jinil; Song, Kyoung; Choi, Joon-Seok; Choi, Yoon-La; Shin, Young Kee (Frontiers in Oncology, 2020)
We previously showed that UBE2C mRNA expression is significantly associated with poor prognosis only in patients with hormone receptor (HR)+/human epidermal growth factor receptor 2 (HER2)− breast cancer. In this study, we further reanalyzed the correlation between UBE2C mRNA expression and clinical outcomes in patients with HR+/HER2− breast cancer, and we investigated the molecular mechanism underlying the role of UBE2C modulation in disease progression in this subgroup of patients. Univariate and multivariate analyses showed that high UBE2C expression was associated with significantly shorter survival of breast cancer patients with pN0 and pN1 tumors but not pN2/N3 tumors (P < 0.05). In vitro functional experiments in HR+/HER2− breast cancer cells showed that UBE2C expression is a tumorigenic factor, and that estrogen upregulated UBE2C mRNA and protein by directly binding to the UBE2C promoter region. UBE2C knockdown inhibited cell proliferation by affecting cell cycle progression, and UBE2C overexpression was associated with estrogen-independent growth. UBE2C depletion markedly increased the cytotoxicity of tamoxifen by inducing apoptosis. The present findings suggest that UBE2C overexpression is correlated with relapse and promotes estrogen-dependent/independent proliferation in early HR+/HER2− breast cancer.